Peningkatan Kemampuan Perangkat Desa Mejasem Timur dalam Tata Kelola Pembukuan dan Kearsipan Administrasi Desa - Rahmadiane, Ghea Dwi; Ita; Pamela; Vivi; Nurul; Cahya; Musfiq (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
The village became one of the focuses in the development of the country. This is evident from the existence of a village budget or village fund that is quite large in number. In terms of office affairs, including in the scope of the Village Office, of course, it does not escape the affairs of administration and require that the workers in the village have skills in good accountancy and archival-management. This community service provides knowledge on good administration archival and accountancy, thus it is hoped that partners in this activity can improve the ability to take care of village office administration. The result of this activity is the increasing insight of workers about the governance of archives but some workers still complain of being less proficient in computer operation.